Melanoma extracellular vesicles generate immunosuppressive myeloid cells by ipregulating PD-L1 via TLR4 signaling - Fleming, Viktor; Hu, Xiaoying; Weller, Céline; Bitsch, Rebekka; Groth, Christopher; Riester, Zeno; Hüser, Laura; Sun, Qian; Nagibin, Vasyl; Kirschning, Carsten; Bronte, Vincenzo; Utikal, Jochen; et al. (Cancer research, 2019)
Tumor cell-derived extracellular vesicles (EV) convert normal myeloid cells into myeloid-derived suppressor cells (MDSC), inhibiting antitumor immune responses. Here, we show that EV from Ret mouse melanoma cells upregulate the expression of programmed cell death ligand 1 (PD-L1) on mouse immature myeloid cells (IMC), leading to suppression of T-cell activation. PD-L1 expression and the immunosuppressive potential of EV-generated MDSC were dependent on the expression of Toll-like receptors (TLR). IMC from Tlr4-/- mice failed to increase T-cell PD-L1 expression and immunosuppression with Ret-EV treatment, and this effect was dependent on heat-shock protein 86 (HSP86) as HSP86-deficient Ret cells could not stimulate PD-L1 expression on normal IMC; IMC from Tlr2-/- and Tlr7-/- mice demonstrated similar results, although to a lesser extent. HSP86-deficient Ret cells slowed tumor progression in vivo associated with decreased frequency of tumor-infiltrating PD-L1+CD11b+Gr1+ MDSC. EV from human melanoma cells upregulated PD-L1 and immunosuppression of normal monocytes dependent on HSP86. These findings highlight a novel EV-mediated mechanism of MDSC generation from normal myeloid cells, suggesting the importance of EV targeting for tumor therapy. SIGNIFICANCE: These findings validate the importance of TLR4 signaling in reprogramming normal myeloid cells into functional myeloid-derived suppressor cells.
Gesehen am 27.02.2020